DINAMIKA KELOMPOK NELAYAN DI KELURAHAN SANGA-SANGA MUARA KECAMATAN SANGA-SANGA KABUPATEN KUTAI KARTANEGARA - Ulfriansyah; eko sugiharto; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The goal of research is to identify the profil of groups and the dynamics of fisheries groups that are in the village Sanga-Sanga Muara districts Sanga-Sanga at Kutai Kartanegara regency. The kind of data retrieval used in this research is the survey method. Primary data sources obtained using primary data and secondary data. As for the indicators of that : group goals, group structures, group functions, group effectiveness, group development or maintenance, group unity and cohesiveness, group atmosphere, group tension. The result of this study indicate that the level of group dynamics that are in the village of village sanga-sanga muara districts of sanga-sanga at Kutai Kartanegara regency with a total score of 72.6 in the high level category.